Using topical benzocaine before lingual frenotomy did not reduce crying and should be discouraged. (29th April 2014) - Ovental, A; Marom, R; Botzer, E; Batscha, N; Dollberg, S
Abstract Aim The US Food and Drug Administration has said that oral preparations containing benzocaine should only be used in infants under strict medical supervision, due to the rare, but potentially fatal, risk of methemoglobinemia. This study aimed to determine the analgesic effect of topical application of benzocaine prior to lingual frenotomy in infants with symptomatic tongue‐tie. We hypothesised that the duration of crying immediately following frenotomy with topical benzocaine would be shorter than with no benzocaine. Methods This randomised controlled study compared the length of crying after lingual frenotomy in term infants who did, or did not, receive topical application of benzocaine to the lingual frenulum prior to the procedure. Results We recruited 21 infants to this study. Crying time was less than one minute in all of the subjects. The average length of crying in the benzocaine group (21.6 ± 13.6 sec) was longer than the length of crying in the control group (13.1 ± 4.0 sec), p = 0.103. Conclusion Contrary to our hypothesis, infants who were treated with topical benzocaine did not benefit from topical analgesia in terms of crying time. The use of benzocaine for analgesia prior to lingual frenotomy in term infants should therefore be discouraged.